The Role of Matrix Metalloproteinase-9 in Lung Function Impairment in Patients with Post-Tuberculosis Sequelae - Rusmini, Hetti; Soemarwoto, Retno Ariza S; Messah, Anse Diana V; Yunus, Faisal; Dilangga, Pad; Herdarto, Muhammad Junus Didiek; Hendarto, Gatot Sudiro; Ekawati, Diyan (Jurnal Respirologi Indonesia, 2026)
Background: Post-tuberculosis (post-TB) sequelae are long-term pulmonary complications that persist despite completion of anti-tuberculosis treatment (ATT). These long-term effects frequently contribute to diminished pulmonary function and a lower quality of life. Matrix metalloproteinase-9 (MMP-9) is thought to be involved in the process of lung tissue injury among individuals recovering from tuberculosis. This study aimed to explore the correlation between serum MMP-9 levels and pulmonary function impairment in post-TB patients. Methods: An observational case-control study was carried out at Dr. H. Abdul Moeloek Hospital in Lampung between April 2023 and March 2024. The study involved 35 post-TB patients (case group) and 35 healthy individuals (control group). Pulmonary function was evaluated using spirometry, while serum MMP-9 concentrations were measured by ELISA. The data were statistically analysed using the Mann-Whitney U test and Spearman's rank correlation. Results: The post-TB group exhibited higher serum MMP-9 levels compared to the control group (1137.7±527.4 vs. 939.5±360.1), though the difference did not reach statistical significance. Post-TB patients showed reduced lung function, particularly in FEV1/FVC, FEV1, and FVC values. There was a significant correlation between MMP-9 levels and pulmonary function parameters, including pre-bronchodilator FEV1/FVC (r = -0.321; P=0.007), post-bronchodilator FEV1/FVC (r = -0.265; P=0.027), and %FEV1 (r = -0.254; P=0.034). Conclusion: Increased serum MMP-9 levels are associated with reduced lung function in post-tuberculosis patients, particularly in cases of obstructive impairment. MMP-9 has the potential to be used as a biomarker for lung injury in individuals with a history of tuberculosis.